Efficacy of simultaneous hexavalent chromium biosorption and nitrogen removal by the aerobic denitrifying bacterium Pseudomonas stutzeri YC-34 from chromium-rich wastewater - Yang, Keyin; Bu, Huijun; Zhang, Ying; Yu, Hongxia; Huang, Sining; Ke, Lixia; Hong, Pei (Frontiers in Microbiology, 2022)
The impact of high concentrations of heavy metals and the loss of functional microorganisms usually affect the nitrogen removal process in wastewater treatment systems. In the study, a unique auto-aggregating aerobic denitrifier (Pseudomonas stutzeri strain YC-34) was isolated with potential applications for Cr(Ⅵ) biosorption and reduction. The nitrogen removal efficiency and denitrification pathway of the strain were determined by measuring the concentration changes of inorganic nitrogen during the culture of the strain and amplifying key denitrification functional genes. The changes in auto-aggregation index, hydrophobicity index, and extracellular polymeric substances (EPS) characteristic index were used to evaluate the auto-aggregation capacity of the strain. Further studies on the mineralization ability and mechanism of cadmium in the process of denitrification were carried out. The changes in tolerance and adsorption index of cadmium were measured and the micro-characteristic changes on the cell surface were analyzed. The strain exhibited excellent denitrification ability, achieving 90.58% nitrogen removal efficiency with 54 mg/L nitrate-nitrogen as the initial nitrogen source and no accumulation of ammonia and nitrite-nitrogen. 30% of the initial nitrate-nitrogen was converted to N2, and only a small amount of N2O was produced. The successful amplification of the denitrification functional genes, norS, norB, norR, and nosZ, further suggested a complete denitrification pathway from nitrate to nitrogen. Furthermore, the strain showed efficient aggregation capacity, with the auto-aggregation and hydrophobicity indices reaching 78.4% and 75.5%, respectively. A large amount of protein-containing EPS was produced. In addition, the strain effectively removed 48.75%, 46.67%, 44.53%, and 39.84% of Cr(VI) with the initial concentrations of 3, 5, 7, and 10 mg/L, respectively, from the nitrogen-containing wastewater. It also could reduce Cr(VI) to the less toxic Cr(III). FTIR measurements and characteristic peak deconvolution analysis demonstrated that the strain had a robust hydrogen-bonded structure with strong intermolecular forces under the stress of high Cr(VI) concentrations. The current results confirm that the novel denitrifier can simultaneously remove nitrogen and chromium and has potential applications in advanced wastewater treatment for the removal of multiple pollutants from sewage.